Bases estruturais da interação da lectina de Canavalia brasiliensis Mart. ex Benth. (ConBr) com o fitohormônio ácido indole-3-acético - Sales, Misrael Vieira (2019)
Lectins are proteins, widely distributed in nature, that recognize and specifically bind to particular carbohydrate structures. Most of their biological properties are related to their ability to interact with saccharides on the cell surface. However, several evidences show that these proteins have affinity for other compounds, mainly hydrophobic molecules, such as phytohormones, which play an important physiological role in the plant. In this context, the construction of this work arose due to the need to investigate the structural interaction of Canavalia brasiliensis (ConBr) seed lectin with the indole-3-acetic acid auxin molecule (AIA). For this, ConBr lectin was co-crystallized with AIA by the steam diffusion method at 18 ºC and the structural stability of the protein / ligand complexes was evaluated by the thermofluor method. The crystallographic structure of ConBr complexed with indole-3-acetic acid was resolved with a resolution of 2.2 Å. Satisfactory refinement had an Rfactor of 0.191 and an Rfree of 0.236. The stereochemical quality of the structure was proven from the Ramachandran chart, showing that no residue was in non-permitted regions. AIA has been found to interact by hydrogen bonding with Ser108 and Asn131 residues in the central cavity of the ConBr tetramer structure. The thermoflour test showed that auxins contribute to an increase in ConBr structural stability at high concentrations. Thus, it can be concluded that the interaction site of ConBr with AIA is conserved when compared with Canavalia maritima lectin, but the positioning of the indole groups of AIA molecules in the ConBr structure makes it impossible to stack hydrophobic interactions between the rings. auxin. In addition, evidence shows that auxins AIA, indole butyric acid (IBA) and 2.4 dichlorophenoxyacetic acid (2.4D) have a low affinity for ConBr.